Studi Literatur: Pengaruh Model Pembelajaran dengan Pendekatan Saintifik Menggunakan Representasi Tetrahedral Kimia terhadap Hasil Belajar Siswa - Eriska Dwi Ananda; Faizah Qurrata Aini (Universitas Negeri Padang, 2022)
This study aims to describe the effect of using scientific approach based learning model on students’ learning outcomes. The method is literature review. The data used in this study is secondary data. This secondary data was obtained from books and scientific articles. The research procedure was carried out through several stages, namely designing the topic and research objective, conducting review, analyzing data, and writing review. The result of this literature study show that the use of Problem Solving and Problem Posing learning models using tetrahedral chemistry representation has an effect on student learning outcome. Other learning models such as Problem Based Learning, Project Based Learning, Constructive controversy, and Guided Inquiry that use tetrahedral chemistry representation do not have a significant effect on student learning outcome. In other words, these four models give the same good result to student learning outcome.